lnfluence of the preparation of the operative field: on the incidence of the post-operative suppuration of the wound - Perrier, José Pedro; Somma, Caren; Torterolo, Edgardo (Cirugía del Uruguay, 1984)
The influence thrt the different ways of preparing the skin area for an operation may have in the prevention of operative wound suppuration, is analysed in a prospectiva study, extended through eight months, with cases chosen at random No difference was found in 189 emergency operations where patients had been shaved for surgery in the six hours immediately before, between desinfection with ether and iodopovirone solution alone or with previous washing of the skin. 437 selected operated patients evidenced that shaving for surgery 2 o 3 hours before or the washing without shaving, of the operation area significantly reduces the incidériées" of infection (p .e 0,02).